Mindfulness and the teachers health (Ágora de Heterodoxias, 2019)
The central focus of this paper was to design an educational intervention program based on Mindfulness as a pedagogical instrument to cope with teaching stress in Obligatory Secondary Education in the public sphere, in Spain. Methodologically, this proposal is supported in a documentary review about Mindfulness, its fundaments and its applicability in the educational context; and the burnout in Spain, especially by those who do their job in Secondary Education. The analysis shows the existence of the problem and we want to offer this program, affirming a series of workshops about Mindfulness and its strategies against stress, based on the components of Mindfulness according to Kabat-Zinn (2003). In the literature review about Mindfulness and its fundaments, a great variety of applications of this practice was found, that start from the Spanish context who have analyzed the stressful circumstances in which teachers operate. The program/proposal was structured in four modules that have the general objective of introducing the Obligatory Secondary Education professors into the theoretical-practical management of Mindfulness and its techniques to deal with the states of work stress and burnout: the activities, time, support materials and the instruments of evaluation are defined in each module
Keywords: Mindfulness; teaching health; focused mind; burnout; teacher stress